Including God in Psychotherapy: Strong Vs. Weak Theism - Slife, Brent D. (Journal of psychology and theology, 2010)
The authors first attempt to conceptualize theistic psychotherapy by discussing the relationship between theism and naturalism. Many psychologists have assumed that naturalism and theism can be combined in various ways, so the authors review the more prominent of these combinations at the outset. They argue not only that these mixtures are “weak” (i.e., they restrain God in some way) but also that they ultimately assume naturalism is incompatible in many ways with theism. The authors compare “weak” theism with a “strong” theism that does not restrain God or rely on naturalistic assumptions. This comparison is elaborated by distinguishing a published example of strongly theistic psychotherapy from three common types of weakly theistic psychotherapy, with corresponding examples from the theistic literature.